NIR active squaraine dyes for dye-sensitized solar cells: modulating aggregation, orientation and electronic properties of the dyes - Bisht, R. (CSIR-National Chemical Laboratory, 2018)
Squaraine dyes are a subclass of polymethine dyes, which owing to its low band gap and strong absorption (ε >105 M−1 cm−1) in the far-red and NIR region have found application in dye-sensitized solar cells. While the squaraine dyes have excellent absorption in the far-red region, the exciton quenching by aggregation limits its overall performance in dye-sensitized solar cells. The aggregates form when the dipoles of the molecules interact with each other due to pi-pi interaction. When a molecule absorbs light and reaches excited state, the photoexcited electron in the LUMO state hops between the neighboring molecules instead of injecting electron in the metal oxide semiconductor. Thus aggregation may hamper the efficiency of DSSC by quenching the exciton which leads to low electron injection on TiO2. Thus it is desirable to have such a design for dyes which can help in controlling aggregation and promote charge injection efficiency in squaraine dyes. It is also beneficial to shift the absorption of squaraine dyes further towards NIR to utilize maximum available photons. It can be achieved by extension of conjugation which can be done either towards the anchoring end or the non-anchoring end. Hence, we designed and synthesized squaraines based dye for DSSC with focus on modulating electronic and steric properties of dyes to enhance absorption in NIR region and avoid aggregation on TiO2 surface respectively. To achieve this, we used moieties like benzodithiophene (BDT), fused fluorenylindolenine and fused indenoquinalidne to enhance absorption and also several in-plane and out-of-the plane alkyl chains were integrated to control aggregation.
Keywords: Dye-sensitized Solar Cells; Modulating aggregation